Diversity Initiatives and White Americans' Perceptions of Racial Victimhood. (June 2022) - Kaiser, Cheryl R.; Dover, Tessa L.; Small, Payton; Xia, Gary; Brady, Laura M.; Major, Brenda
Seven experiments explore whether organizational diversity initiatives heighten White Americans' concerns about the respect and value afforded toward their racial group and increase their perceptions of anti-White bias. The presence (vs. absence) of organizational diversity initiatives (i.e., diversity awards, diversity training, diversity mission statements) caused White Americans to perceive Whites as less respected and valued than Blacks and to blame a White man's rejection for a promotion on anti-White bias. Several moderators were tested, including evidence that Whites were clearly advantaged within the organization, that the rejected White candidate was less meritorious than the Black candidate, that promotion opportunities were abundant (vs. scarce), and individual differences related to support for the status hierarchy and identification with Whites. There was little evidence that these moderators reduced Whites' perceptions of diversity initiatives as harmful to their racial group.